Selective Laser Melting Of Nickel Base Heat Resistance Alloy EP648 - Nerush, S. V. (2016)
For successful development of selective laser melting technology, it is important to increase the range of suitable materials. One of the most interesting materials for aerospace, automotive, shipbuilding and energy industries is heat-resistance superalloys. In this research EP648 nickel base heat resistance alloy was used for SLM. For determination of influence of SLM process parameters on EP648 4x4x4 mm cubic specimens were fabricated in SINTERSTATION® Pro DM125 SLM machine by using different process parameters (laser power, layer thickness, point distance, exposure time). The porosity of fabricated specimens was determined by scanning electron microscopy of polished cross-sections. SLM mode with lowest porosity (less than 1%) was selected for produce specimens for tensile strength tests. Tensile tests were carried out by using Gleeble 3800 Thermal-Mechanical Testing System for different test temperatures (up to 1073 K). Results of tests (ultimate tensile strength) showed that SLM produced EP648 by mechanical properties not inferior to cast material.